Altruism to strangers for our own sake: domestic effects from immigration: A comparative analysis for EU15. Issue 1 (2014) - ,; ,
Abstract : Purpose – Theoretical and empirical research on the impact of immigrants for local development is rather inconclusive regarding the direction of said impact. The purpose of this paper is to identify relationships between human capital and cultural capital, in the context of local labour market productivity.Design/methodology/approach – As the key constituents of human capital, identified in the literature, are both the locally generated through investment in education and the inflowing through immigration human capital, the paper examines those jointly in a close‐to‐reality‐model. To this end, the paper operationalizes and infers data on the "melting pot" of EU15, NUTS2 level. The sources of the data are the Eurostat Regional Database and the World Value Survey, which have served to construct both a cross‐section for the year 2001. These data sets allows us to examine the different groups of migrating and local human capital, their interaction and joint impact on local productivity through three stage least square estimations of the simultaneous equations CBD model.Findings – The evidence suggests that benefits from immigrants differ, not only due to their human capital, but also due to their culturally biased different bargaining power on the labour market.Originality/value – The main advantage of the suggested model of productivity is that, in addition to accounting for the filigree composition of human capital, it also takes into consideration the cultural capital present in a locality. In this manner, the authors are able to examine the interaction between the quality of the incoming human capital and the cultural encounter context (generating the cultural "milieu" effect) of the modern diverse city.